The Influence of Price and Product Quality on Interest in Buying Online Skincare Moderated by Influencers on Tiktok Shop (Case Study on Juva by Zap Skincare Products) - Putri Dewi, Dita Eka Sartika; Widjaja, Bernard T.; Widodo, Rintis Eko (Syntax Literate, 2026)
This study aims to analyze the influence of product quality and price on the interest in buying online skincare products Juva by ZAP on the TikTok Shop platform with influencers as a moderation variable. This study uses a quantitative method with a positivistic approach and data collection through an online questionnaire using the Likert scale. The research sample consisted of 160 respondents who had bought skincare products through TikTok Shop. Data were analyzed using SPSS for descriptive analysis and WarpPLS for inferential analysis. The results of the study show that product quality has a positive and significant effect on buying interest, meaning that the better the quality felt by consumers, the higher the buying interest that arises. Similarly, price has been proven to have a positive and significant effect on buying interest, so competitive prices are an important factor in attracting purchase decisions. However, influencer variables do not moderate the relationship between product quality and buying interest, so the presence of influencers does not reinforce the influence of quality on purchasing decisions. On the other hand, influencers have been shown to moderate the relationship between price and buying interest in a negative direction, which means that the existence of influencers can actually weaken the influence of price on buying interest. These findings underscore the importance of marketing strategies that emphasize product quality, proper pricing, and the selection of credible, relevant, and appropriate influencers in accordance with the characteristics of the target market.